The influence of career development, work motivation, and job satisfaction on employee performance at X Resort Barelang Batam - Tedi Kurnia Putra; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2026)
This study investigates the influence of career development, work motivation, and job satisfaction on employee performance at X Resort Barelang Batam, a four-star hospitality establishment operating under The Ascott Limited network. Using a quantitative approach with 85 respondents and statistical analysis conducted through SPSS 25, the research aims to determine the extent to which these human resource variables contribute to performance outcomes. The results reveal that all three independent variables—career development (X₁), work motivation (X₂), and job satisfaction (X₃)—have positive and significant effects on employee performance (Y). Among them, job satisfaction demonstrates the strongest influence (β = 0.308; Sig = 0.002), followed by work motivation (β = 0.305; Sig = 0.005) and career development (β = 0.136; Sig = 0.198). The model’s coefficient of determination (R² = 0.601) indicates that 60.1% of performance variation is explained by these factors. The findings highlight that structured career development, effective motivational strategies, and enhanced job satisfaction collectively strengthen employee engagement and service quality. These results confirm the theoretical propositions of human capital and expectancy theories while providing practical implications for improving human resource policies within the hospitality sector.